Engineering ethnic and political tolerance on voters choice - Nizah M.A.M.; Norawavi A.N.; Kandil H.M.T.E.; Adibah Sulaiman (IAEME Publication, 2024)
Tolerance considered an essential element in the modern multicultural society. Empirical evidences confirmed that tolerance has a positive effect towards social stability and harmony. However, there is insufficient study on direct influence of ethnic and political tolerance on people voting decision. This study is conducted to explore the influence of ethnic and political tolerance on voters choice. This survey study using self-administered questionnaire as a data collection technique. Data were analysed using Structural Equation Modelling (SEM). 600 respondents were engaged in the survey using multistage cluster and random sampling techniques involving voters in three different parliamentary. Results revealed that level of education, party supported and ethnicity had a significant positive influence on voting behaviour. Ethnic tolerance had a significant relationship with voting behaviour, while political tolerance is not statistically significant. But both, ethnic tolerance and political tolerance had a significant positive correlational relationship. Therefore, it is apparent that ethnic and political tolerance has a considerable effect on of voting behaviour. Significances are varies which demographics ethnicities act as intercession factors. The current study filled the gap to the body of knowledge and allows countless implication where ethnic politics regards as the most imperative matter, and tolerance has progressively become Malaysias national agenda in managing a multicultural society. IAEME Publication.